(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Diabetes mellitus is a chronic metabolic disorder and is becoming the world’s third “killer” together with cancer, cerebro and cardiovascular diseases due to its wide spread prevalence, morbidity and mortality. Modern anti-diabetic agents produce undesirable adverse effects. As a result, alternative therapy is required. A shift towards marine natural products is desperately needed. Hence, this research was carried to examine the antidiabetic activity of methanolic extract of Turbinella pyrum. Alloxan was induced to get experimental diabetes animals in albino rats. A comparison was made between the action of methanolic extract of Turbinella pyrum extracts and a known antidiabetic drug glibenclamide (600 μg/kg body wt). An oral glucose tolerance test (OGTT) was also performed in experimental diabetic rats. The diabetic rats were randomly divided into four groups (n=6/group). Group I served as control and received distilled water. Group II served as standard (Glibenclamide 600μg/kg). Group III and IV received the methanolic extract of Turbinella pyrum at a dose of 200mg/kg and 400mg/kg respectively. Maximum effect was observed at 3 hours with the low (200 mg/kg) and high (400 mg/kg) doses of methanolic extract of Turbinella pyrum which exerted more pronounced effects (87.33mg/dl and 57.17mg/dl). The effects of methanolic extract of Turbinella pyrum were more than that of the standard drug glibenclamide. Treatment of diabetic rats with the methanolic extract of Turbinella pyrum improved the body weight that is 15.49g and 16.75g at 200 and 400mg/kg doses respectively. The glibenclamide treated diabetic rats also showed improved body weight (13.88). These results demonstrate significant antidiabetic potential of the methanolic extract of Turbinella pyrum (p<0.01) and can be used for drug production in pharmaceutical industries.